Analisis Kinerja Turbocharger pada saat Beban Maksimum Menggunakan Metode RCFA (Root Cause Failure Analysis) di PLTMG Arun - Furqan Muhammad Nur; Saifuddin Saifuddin; Muhammad Sami (Jurnal Teknologi, 2023)
Gas engine power plant (PLTMG) is a power plant that uses a gas engine as the prime mover. Prime mover is equipment that has the function of generating the mechanical energy needed to rotate the generator rotor. The Arun PLTMG uses a type 20V34SG wartsila gas engine as the main engine. The 20V34SG type Wartsila engine has replaced several components but has not made the engine performance efficient again. One of the important components in supporting the electricity production process is the turbocharger. A turbocharger is a centrifugal compressor that gets power from a turbine whose power source comes from vehicle exhaust fumes. Usually used in internal combustion engines to increase power output and engine efficiency by increasing the air pressure entering the engine. The purpose of this paper is to calculate the efficiency of the equipment and analyze the results using the RCFA (Root Cause Failure Analysis) method to find out the basic problems that occur in the turbocharger. Based on the results of the calculation analysis showed that the lowest efficiency value for turbocharger A occurred in engine 14, which was 57%, and for turbocharger B efficiency, it was found in engine 13, which only reached 54%. By observing in the field there is oil seepage from the turbocharger which falls into the charge air cooler (CAC) area, wear and tear on the impeller mechanical sealing.